Ancient and historical DNA in conservation policy. (May 2022) - Jensen, Evelyn L.; Díez-del-Molino, David; Gilbert, M. Thomas P.; Bertola, Laura D.; Borges, Filipa; Cubric-Curik, Vlatka; de Navascués, Miguel; Frandsen, Peter; Heuertz, Myriam; Hvilsom, Christina; Jiménez-Mena, Belén; Miettinen, Antti; et al.
Abstract : Although genetic diversity has been recognized as a key component of biodiversity since the first Convention on Biological Diversity (CBD) in 1993, it has rarely been included in conservation policies and regulations. Even less appreciated is the role that ancient and historical DNA (aDNA and hDNA, respectively) could play in unlocking the temporal dimension of genetic diversity, allowing key conservation issues to be resolved, including setting baselines for intraspecies genetic diversity, estimating changes in effective population size ( Ne), and identifying the genealogical continuity of populations. Here, we discuss how genetic information from ancient and historical specimens can play a central role in preserving biodiversity and highlight specific conservation policies that could incorporate such data to help countries meet their CBD obligations. Highlights: Genetic diversity within species and populations is necessary for long-term survival and thus constitutes a key component of preserving biodiversity, but until now, it has rarely been integrated into conservation policies. Ancient and historical genetic data [ancient/historical DNA (a/hDNA)], such as those from specimens stored in natural history collections, can add a temporal dimension to conservation genetic inferences by providing baseline levels of diversity that contemporary data can be compared with and help guide conservation actions. To increase the use and impact of a/hDNA research in preserving biodiversity, genetic indicators must be explicitly included in conservation policies, the benefits and limitations of using a/hDNA need to be clearly communicated to all conservation actors, and relationships between academics, museums, conservation practitioners, and policy makers must be strengthened.